Intoxicação aguda por agrotóxicos : um estudo do registro nas regiões agrícolas do agronegócio - Lara, Stephanie Sommerfeld de (2018)
Brazil is a large agricultural producer that in recent decades has been using pesticides on a large scale in the fight against agricultural pathologies, and consequently, it is the world leader in consumption. The state of Mato Grosso is the largest national consumer of this toxicant, exposing workers, the rural and urban population to millions of liters sprayed on crops, which contaminate food, water, soil and all surrounding environment. This human exposure to pesticides can lead to acute intoxication, an important public health problem that has become common in Brazil. However, the high underreporting of cases makes it impossible to trace the pattern of occurrence in the territories, as well as to verify the connection between agribusiness agricultural production, agrochemical consumption and injurie. The objective was to analyze the record of acute intoxication by pesticides and correlate them with the consumption of pesticides in agricultural production of agribusiness. It is an observational epidemiological study, being the first one of ecological design and the second descriptive. The secondary data of agricultural production were obtained SIDRA-IBGE referring to the year 2015. The consumption of pesticides was estimated through the methodology of Pignati et al. (2017). The notification of intoxication was obtained from SINAN-MS in the period from 2007 to 2016. The results showed that in Brazil, poisoning by pesticides ranked second among all exogenous ones, with an increasing number of cases and incidence over the years, presenting high lethality among all toxic agents. It was positively and significantly associated with the consumption of pesticides and environmental exposure with the average incidences of intoxication by agricultural pesticides, both for the Federated Units and for the municipalities of Mato Grosso. In the second article, occupational poisoning in Mato Grosso occurred predominantly with agricultural and public health pesticides. It was in the soybean crop that there were the highest number of occupational intoxications, later that of maize, rice, pasture and cotton. There were 4 deaths caused by the exposure of agricultural pesticides. Of the 141 municipalities in Mato Grosso, 83 reported occupational poisoning by agricultural pesticides and the 54 municipalities characterized as a zone of high agricultural cultivation, 14 of them remained silent over the 10 years. Agricultural pesticide poisonings and used in Public Health occurred predominantly in the accidental form. CAT was emitted in 10% of the occupational intoxications reported by SINAN. It is concluded that acute intoxication by pesticides is correlated with the use of pesticides in monocultures and the environmental exposure of these products in the municipalities of Mato Grosso, with soybeans being concentrated in the highest number of occupational intoxications. Although the record of intoxications is still incomplete in quality and quantity, we suggest that such findings be used by the Vigilance in Worker Health and Populations Exposed to Pesticides in the implementation and implementation of strategic actions in these municipalities with high agricultural production, consumption of pesticides and cases of acute intoxication.